Dança contemporânea na preparação do ator: reflexões a partir da preparação corporal do espetáculo "O guesa errante" - Cristiano de Sousa Reis (2011)
This research investigated how Contemporary Dance, as a knowledge field that uses a varied repertoire of methods and techniques can be used in the corporal preparation of actors. For this, it has located in history some thoughts of the main producers and choreographers ofthe end of 19th century and beginning of 20th century that had breached with the traditional/classical form to think the body in dance and theater. It presents some conceptions of what it comes to be the Contemporary Dance, its methods, techniques and its slight knowledge of body. It uses the experience of the corporal preparation undertaken in the spectacle the Nomadic Guesa (Guesa Errante), to reflect on the use of the Contemporary Dance in the corporal preparation of actors. This experience allowed recognizing five linked moments: corporal unpreparedness, reconstruction and corporal reorganization, our dailyground, the discovery of the spiral, the conquest of the dancing body and a basis tripod that potentiates all the phases. The analysis of these moments made possible to evidence that, in the corporal preparation, the Contemporary Dance established a place that the actor could recognize and try his own body as a technical instrument and as a way to know himself, favoring the artistic expression. The body as the way and result of its art.